The bat Tonatia bidens (Phyllostomidae) as an insect pest predator in the Brazilian Caatinga - Barbier, Eder [UNESP]; Nobre, Carlos Eduardo Beserra; Iannuzzi, Luciana; Bernard, Enrico (Walter De Gruyter Gmbh, 2024)
Tonatia bidens is listed as 'Data Deficient' in the IUCN Red List. Our research, conducted in the Brazilian Caatinga dry forest between 2016 and 2022, aimed to shed light on the diet of this little-known species. Thirty-eight taxa were identified among insect remains beneath T. bidens' feeding perch. Notably, certain insects such as hawkmoths and cerambycid beetles are agricultural pests with significant negative impacts on crops, including cassava, corn, tomato, papaya, and cashew plantations. These results underscore bats' crucial role in insect pest consumption, emphasizing the need for further studies to fully understand their diet and ecosystem contributions.
Keywords: Chiroptera; ecosystem services; insect pest consumption; Coleoptera; Lepidoptera